Is anti-herding always a smart choice? Evidence from mutual funds - LEE, John Byong-Tek (Institutional Knowledge at Singapore Management University, 2023)
Recent empirical studies document a negative relation between herding behaviour and the skill of mutual fund managers. We explore this relationship further by focusing on fund managers' contrarian buy and sell behaviour against the market. Our study reveals an asymmetry in the performance of mutual funds with contrarian buy behaviour and contrarian sell behaviour. The contrarian-buy behaviour reflects skill by positively predicting the cross-section of next period's mutual fund returns, while the contrarian-sell behaviour reflects a lack of skill associated with a negative prediction. These findings are robust to various risk-adjusted performance measures. Contrarian-buy funds outperform momentum-buy funds by 3% per year, while contrarian-sell funds underperform momentum-sell peers by about 4%. These findings are robust across different sizes and styles of mutual funds. Further analysis indicates that the asymmetric effect is reversed during recessions and disappears when market sentiment is high. We also study how mutual fund characteristics relate to contrarian buy and sell practices. We find that mutual funds with larger size, higher flow, lower tracking error, and no manager ownership are more likely to buy against the crowd but sell with the crowd.